2) 1-sin2x=cosx-sinx (cosx-sinx)²=cosx-sinx (cosx-sinx)²-(cosx-sinx )=0 (cosx-sinx)(cosx-sinx-1)=0 a) cosx-sinx=0 1-tgx=0 tgx=1 x1=π/4+πn б) cosx-sinx-1=0 cos²(x/2)-sin²(x/2)-2sin(x/2)cos(x/2)-cos²(x/2)-sin²(x/2)=0 -2sin²(x/2)-2sin(x/2)cos(x/2)=0 2sin(x/2)(sin(x/2)-cos(x/2))=0 sin(x/2)=0 x/2=πn x2=2πn sin(x/2)-cos(x/2)=0 tg(x/2)=1 x/2=π/4+πn x3=π/2+2πn

Ответы и объяснения

Лучший Ответ!
2014-04-09T20:25:10+04:00
Cos2x=cosx-sinx (cosx-sinx)(cosx+sinx-1)=0 1)cosx-sinx=0(:cosx) (cosx-sinx)(cosx+sinx)=cosx-sinx tgx=1, x1=П/4 +Пп, пЄZ 2)cosx+sinx-1=0 cosx+cos(П/2-x)=1 2cos(П/4)cosx=1 2*v2/2*cosx=1 v2cosx=1 cosx=1/v2 x2=+-П/4 +2Пп, пЄZ